Efektivitas Konseling Kelompok Dengan Menggunakan Teknik Rational Emotive Behavior Therapy Dalam Meningkatkan Self-Convidence Andikpas Di LPKA Kelas I Palembang - Utami, Sri; Jannati, Zhila; Kusnandi, Kusnandi (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
esearch is a quantitative experimental research. The questionnaire is the first instrument in data collection by distributing a number of questions to ANDIKPAS regarding self-confidence. Meanwhile, the supporting methods are observation and documentation. The research subjects were ANDIKPAS in Class I LPKA Palembang totaling 8 people. The data analysis technique used is descriptive statistics. The results of this study found that the average on the Self Confidence pretest was 136.50, and decreased to 164.00 on the Self Confidence posttest or increased by 27.50. So there is a difference in the average Self Confidence before and after group counseling treatment, has a t count value of 5.811 > t table with df (0.05, 8) = 2.30, and Sig. = 0.001 which is less than 0.05, meaning that there is a difference in the average Self Confidence before and after group counseling. The correlation value of the pretest and posttest Self Confidence values ​​is 0.741, with a Sig value of 0.036. This means that there is a significant relationship between the pretest and posttest Self Confidence scores with the level of strong closeness. Group counseling using the REBT technique is effective in increasing ANDIKPAS self-confidence, increasing the abilities possessed by ANDIKPAS.